Preparation, characterization, and water-sorption study of polyvinyl alcohol based hydrogels with grafted hydrophilic and hydrophobic segments - Shukla, S.; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2005)
The interpenetrating polymer network hydrogels based on poly(vinyl alcohol) were obtained by graft copolymerization of acrylamide and styrene onto polyvinyl alcohol in the presence of N,N'-methylene bisacrylamide as a crosslinking agent. The hydrogels were characterized by optical microscopy, scanning electron microscopy, infrared spectral analysis, differential scanning calorimeter, and thermogravimetric analysis. The hydrogels showed enormous swelling in aqueous medium and displayed swelling characteristics, which were highly dependent on the chemical composition of the hydrogels and pH of the swelling medium. The kinetics of water uptake and the mechanisms of water transport were studied as a function of composition of the hydrogel and pH of the swelling medium. (C) 2005 Wiley Periodicals, Inc.
Keywords: Characterization; equilibrium swelling; grafting; IPN hydrogels; polyvinyl alcohol

Grafting reactions of living macroanions with multi-walled carbon nanotubes - Baskaran, Durairaj; Sakellariou, Georgios; Mays, Jimmy W.; Bratcher, Matthew S. (Journal of Nanoscience and Nanotechnology, 2007)
Grafting reactions of living polystyryllithium (PSLi) with acid chloride containing multi-walled carbon nanotubes (MWNTs-COCl) were performed under vacuum in benzene at room temperature. Covalent grafting of polystyrene (PS) was characterized using spectroscopic, microscopic, and thermogravimetric analyses. Grafting at different ratios of macroanion to acylchloride of the carbon nanotubes showed that the grafting efficiency was not dependent on the concentration of the macroanions. The mole percent of PS present in the MWNTs-g-PS samples was inversely proportional to the precursor molecular weight of PSLi. Direct reactions of PSLi, polybutadienyllithium and n-butyllithium with pristine MWNTs without any functional groups were also performed in the presence and in the absence of tetrahydrofuran in benzene. The grafting reactions of living macroanions either with MWNTs-COCl or with pristine MWNTs indicated a partial grafting of polymer on the carbon nanotubes in benzene at room temperature.
Keywords: Anionic polymerization; covalent functionalization; grafting; multi-walled carbon nanotubes

Carbon dioxide capture using amine functionalized silica gel - Sakpal, Tushar; Kumar, Asheesh; Kamble, Sanjay; Kumar, Rajnish (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Commercially available silica gel is chemically modified for carbon dioxide capture. Calcinated silica gel of certain particle size functionalized with amine using two different methods, wet impregnation and grafting via silane chemistry has been employed as a porous media. The prepared material is characterized by Fourier transform infrared, scanning electron microscopy, energy dispersive analysis of X-rays, thermogravimetry and N-2 physisorption techniques. Gas uptake measurements have been carried out to ascertain the CO2 capture capacity of the amine functionalized material. The experiments have been carried out at moderate pressure and temperature range to ascertain its potential for easy scale up.
Keywords: Amine functionalized silica gel; Carbon dioxide capture; grafting; Poly(ethyleneimine); Silane chemistry; Wet impregnation

Copolymerization of ethylene with unsaturated alcohols and methylmethacrylate using a silylated alpha-diimine nickel catalyst: molecular modeling and photodegradation studies - Matos, Ines; Fernandes, Susete N.; Liu, Hua-Rong; Tevtia, Amit K.; Singh, R. P.; Manda, Lemos; Lemos, Francisco; Marques, Maria M. (Journal of Applied Polymer Science, 2013)
In this article, the experimental results obtained in the copolymerization of ethylene with polar monomers using a silylated -diimine nickel catalyst are described and compared with those obtained with a non-silylate similar one. The results show that the introduction of a siliyl group in the para-position of the imine moiety turns the catalyst less sensitive toward polar functionalities. However, the reactivity observed in copolymerization reactions was found to be reduced both the global polymerization and incorporation rates. Molecular modeling calculation allowed us to understand both the preferred insertion mode and the intermediate product structures for E/MMA copolymerization. Photodegradation studies showed that the presence of polar groups in the copolymers increases their rate of oxidation and turn them more easily degradable. The stabilization performed by Tinuvin 770 showed that for long-exposure times, it is not very effective regardless it is only mixed or grafted to the copolymer. (c) 2012 Wiley Periodicals, Inc.
Keywords: ageing; copolymers; Degradation; grafting

Hydrophobic WO3/SiO2 catalyst for the nitration of aromatics in liquid phase - Kulal, A. B.; Kasabe, M. M.; Jadhav, P. V.; Dongare, M. K.; Umbarkar, S. B. (Applied Catalysis A-General, 2019)
WO3/SiO2 solid acid catalyst synthesized using sol gel method has shown promising activity (up to 65% conversion) for aromatic nitration in liquid phase using commercial nitric acid (70%) as nitrating agent without using any sulfuric acid. The water formed during the reaction as well as water from dilute nitric acid (70%) was removed azeotropically, however due to the hydrophilic nature of the catalyst, some water gets strongly adsorbed on catalyst surface forming a barrier layer between catalyst and organics. This prevents effective adsorption of substrate on catalyst surface for its subsequent reaction. To improve the activity further, the hydrophilic/hydrophobic nature of the catalyst was altered by post modification by grafting with commercial short chain organosilane (Dynasylan 9896). The modified 20% WO3/SiO2 catalyst when used for o-xylene nitration in liquid phase, showed significant increase in the conversion from 65% to 80% under identical reaction conditions. Catalyst characterization revealed decrease in the surface area of 20% WO3/SiO2 from 356 m(2)/g to 302 m(2)/g after grafting with Dynasylan 9896. The fine dispersion of WO3 particles (2-5 run) on silica support was not affected due to modification. NMR and FTIR study revealed the decrease in surface hydroxyl groups imparting hydrophobicity to the catalyst. Interestingly the total acidic sites of the catalyst remained almost unaltered (0.54 mmol NH3/g) even after modification. Even though, the acidity and other characteristics of the catalyst did not change appreciably, there was a considerable increase in the o-xylene conversion which can be ascribed to the hydrophobic nature of the catalyst.
Keywords: Aromatic nitration; grafting; heterogeneous catalysis; Hydrophobic; Sol-gel synthesis

Comparative proteomics unravels the differences in salt stress response of own-rooted and 110R-grafted thompson seedless grapevines - Patil, Sucheta; Shinde, Manisha; Prashant, Ramya; Kadoo, Narendra; Upadhyay, Anuradha; Gupta, Vidya (Journal of Proteome Research, 2020)
Thompson Seedless, a commonly grown table grape variety, is sensitive to salinity when grown on its own roots, and therefore, it is frequently grafted onto salinity-tolerant wild grapevine rootstocks. Rising soil salinity is a growing concern in irrigated agricultural systems. The accumulation of salts near the root zone severely hampers plant growth, leading to a decrease in the productive lifespan of grapevine and causing heavy yield losses to the farmer. In the present study, we investigated the differences in response to salinity between own-rooted Thompson Seedless (TSOR) and 110R-grafted Thompson Seedless (TS110R) grapevines, wherein 110R is reported to be a salt-tolerant rootstock. The grapevines were subjected to salt stress by treating them with a 150 mM NaCl solution. The stress-induced changes in protein abundance were investigated using a label-free shotgun proteomics approach at three time points viz. 6 h, 48 h, and 7 days of salt treatment. A total of 2793 proteins were identified, of which 246 were differentially abundant at various time-points in TSOR and TS110R vines. The abundance of proteins involved in several biological processes such as photosynthesis, amino acid metabolism, translation, chlorophyll biosynthesis, and generation of precursor metabolites was significantly affected by salt stress in both the vines but at different stages of stress. The results revealed that TSOR vines responded fervently to salt stress, while TS110R vines adopted a preventive approach. The findings of this study add to the knowledge of salinity response in woody and grafted plants and hence open the scope for further studies on salt stress-specific differences induced by grafting.
Keywords: 110R rootstock; gene ontology; grafting; label-free proteomics; salt stress; Vitis vinifera